Diseño de un sistema de riego para pastizales a través de un mecanismo de rueda hidráulica y bomba de pistón para el sector “Sharve” de la parroquia El Cisne - Paccha Paccha, Bryan Marcelo (2023)
The present degree work pretends to design an irrigation system, using a hydraulic wheel and piston pump mechanism. Its operation is based on raising the water from the tributary to a deposit and later supplying it to the grass crop. In addition, using the method of the Food and Agriculture Organization of the United Nations (FAO) the amount of water that must be provided in each irrigation is established, thus maintaining the crop at its maximum production. The open channel methodology allows for determining the flow and volume of a natural tributary; likewise, evaluating the difference in flow rates provided by different cross-sections applied. It is determined that the volume provided by the tributary satisfies the demand for irrigation and the operation of the hydraulic wheel. The objective of the work is to know the sizing of the hydraulic wheel that meets the demand required by the selected ZM piston pump, with the number of buckets, wheel diameters, and wheel width. The results obtained in both the agronomic design and the hydraulic design are reliable since the comparisons made with the simulations in the CROPWAT and EPANET software reflect values consistent with the mathematical methods and the sprinkler operating parameters. On the other hand, the hydraulic wheel of metallic and wooden profiles satisfies the ZM pump, given that the results obtained in the design are satisfactory in comparison with existing metallic wheels in the Faculty of Energy of the National University of Loja. Keywords: Irrigation, Food and Agriculture Organization of the United Nations (FAO), Canal Hydraulics, EPANET, hydraulic wheel.